Analysis Of Foreign Debt and Foreign Investment On Economic Growth - Angelina WULANDARI; Ni Putu Rediatni GIRI; A.A Ketut JAYAWARSA (Journal of Tourism Economics and Policy, 2021)
This study examines the influence of foreign debt and foreign investment on economic growth in Indonesia from 2015 to 2020. The study was conducted with a quantitative approach. The research sample was conducted in 2 cities, namely, Malang and Jogjakarta with 200 respondents. Analysis tool using Structural Equation Modeling. The results of the study state that foreign debt has a positive and insignificant effect on economic growth in Indonesia, Foreign investment has a positive and significant impact on economic growth in Indonesia. The government needs to take steps to reduce foreign debt and try to increase investment in Indonesia so that development in Indonesia is more advanced. The government needs to increase foreign investment to support economic growth.